2020
DOI: 10.1371/journal.pgen.1008643
|View full text |Cite
|
Sign up to set email alerts
|

Variants encoding a restricted carboxy-terminal domain of SLC12A2 cause hereditary hearing loss in humans

Abstract: Hereditary hearing loss is challenging to diagnose because of the heterogeneity of the causative genes. Further, some genes involved in hereditary hearing loss have yet to be identified. Using whole-exome analysis of three families with congenital, severe-to-profound hearing loss, we identified a missense variant of SLC12A2 in five affected members of one family showing a dominant inheritance mode, along with de novo splice-site and missense variants of SLC12A2 in two sporadic cases, as promising candidates as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…Because her fibroblasts were collected, genetic analysis revealed that she carried both her parent's mutations. Evidence is now mounting that de novo (single allele) mutations lead to neurodevelopmental deficits and cochlea-vestibular defects (McNeill et al, 2020;Mutai et al, 2020). Another patient with NKCC1 mutation deserves some attention in the context of this review article.…”
Section: Na + /Glucose Transporter (Sglt)mentioning
confidence: 99%
“…Because her fibroblasts were collected, genetic analysis revealed that she carried both her parent's mutations. Evidence is now mounting that de novo (single allele) mutations lead to neurodevelopmental deficits and cochlea-vestibular defects (McNeill et al, 2020;Mutai et al, 2020). Another patient with NKCC1 mutation deserves some attention in the context of this review article.…”
Section: Na + /Glucose Transporter (Sglt)mentioning
confidence: 99%
“…The shaker-with-syndactylism homozygotes are deaf and exhibit vestibular dysfunction [57,58]. So far, several human mutations of NKCC1 have been reported [59][60][61][62][63][64]. Patients with deletion in NKCC1 suffer from multiorgan failure [60] or global developmental delay, together with hearing loss, gastrointestinal abnormalities, and absent salivation (named Kilquist syndrome [59]), while a gain-of-function missense variant of NKCC1 has been linked to schizophrenia [62].…”
Section: Nkcc1 Functions Outside the Cnsmentioning
confidence: 99%
“…The affected individuals presented with severe hearing loss. 98 In the first family, a 7-month-old female infant and her twin brother shared a SLC12A2 c.2145C > G variant, resulting in p.Asp981Tyr mutation. In the second family, the affected individual carried a c.2930-2A > G mutation; which affects the splice acceptor site of exon 21.…”
Section: Slc12a2 Haplotype Insufficiency and Hearing Lossmentioning
confidence: 99%
“…Interestingly, all these variants were confined to exon 21 ( Figure 5 ). 98 In addition to the hearing loss, affected infants in two families had difficulties in holding their heads up, maintaining a sitting position, or walking, indicative of minor motor developmental delays. In a second study, we identified three individuals from two independent families with mutations in exon 21 associated with nonsyndromic bilateral sensorineural deafness ( Table 2 ).…”
Section: Slc12a2 Haplotype Insufficiency and Hearing Lossmentioning
confidence: 99%